2015
DOI: 10.1128/iai.00993-15
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 Modulates Antigen Presentation by Dendritic Cells through Regulation of NLRP3 Inflammasome Assembly during Chlamydia Infection

Abstract: e Interleukin-10 (IL-10) has been implicated in susceptibility to genital chlamydial infection and the development of tubal pathologies. IL-10 limitation also resulted in the rapid elicitation of immune responses against Chlamydia, and decreased levels of IL-10 correlated with protective anti-Chlamydia immunity. To investigate the molecular basis for these effects, we compared the reproductive pathologies and fertility rates in Chlamydia-infected wild-type (WT) and IL-10-knockout (IL-10 ؊/؊ ) mice; we also ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 45 publications
1
22
1
Order By: Relevance
“…The finding mentioned in the former study is supported at least partially by the observed inflammasome-mediated pyroptosis of Chlamydia -exposed antigen presentation cells, which are critical in Chlamydia clearance (38). However, a later study has its own limitations as the results were obtained in IL-10 −/− dendritic cells (DCs) and no direct observations were made in cells lacking inflammasome components.…”
Section: Chlamydia Infectionmentioning
confidence: 67%
“…The finding mentioned in the former study is supported at least partially by the observed inflammasome-mediated pyroptosis of Chlamydia -exposed antigen presentation cells, which are critical in Chlamydia clearance (38). However, a later study has its own limitations as the results were obtained in IL-10 −/− dendritic cells (DCs) and no direct observations were made in cells lacking inflammasome components.…”
Section: Chlamydia Infectionmentioning
confidence: 67%
“…Those alterations in metabolism are required to meet the increased biosynthetic and bioenergetic demands of activated DCs specifically by funneling metabolites into pathways for lipid and protein synthesis [14, 3033]. Disruption of glycolysis through the reduced expression of ENO1 has recently been linked to NLRP3 activation [23], and we have previously shown that NLRP3 inflammasome assembly was suppressed in IL-10 −/− DCs [18], which we now know to have abundantly expressed ENO1, this shows an interesting linkage of ENO1 to the inflammasome that would be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…If correct, this hypothesis implies that C. trachomatis, like N. gonorrhoeae, has the ability to suppress or at least delay the onset of immune responses that might be effective against it, and that eventually the host immune system might break through and mount protective responses. IL-10 induced by Chlamydia has been found to modulate antigen-presentation by dendritic cells and drive them into a regulatory response mode, and in its absence, Chlamydia is more rapidly cleared (Omosun et al 2015).…”
Section: Chlamydiamentioning
confidence: 99%